2010
DOI: 10.2166/nh.2010.004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution-based scaling to improve usability of regional climate model projections for hydrological climate change impacts studies

Abstract: As climate change could have considerable influence on hydrology and corresponding water management, appropriate climate change inputs should be used for assessing future impacts.Although the performance of regional climate models (RCMs) has improved over time, systematic model biases still constrain the direct use of RCM output for hydrotogical impact studies. To address this, a distribution-based scaling (DBS) approach was developed that adjusts precipitation and temperature from RCMs to better reflect obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
209
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(227 citation statements)
references
References 5 publications
4
209
0
4
Order By: Relevance
“…Both projections simulated effects of the A1B emission scenario (Nakićenović et al, 2000), and the GCM results were dynamically downscaled to 50 km using the regional climate model (RCM) called RCA3 (Samuelsson et al, 2011). Thereafter, daily surface temperatures (at 2 m) and precipitation were further downscaled to 4 km, and bias was corrected using the distribution-based scaling method (Yang et al, 2010) with reference data from the 4 km grid-based observations for 1981-2010. Finally, gridded values were transferred to each subbasin for the period 1961-2100 to force the S-HYPE model.…”
Section: Model Approach To the Past And The Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Both projections simulated effects of the A1B emission scenario (Nakićenović et al, 2000), and the GCM results were dynamically downscaled to 50 km using the regional climate model (RCM) called RCA3 (Samuelsson et al, 2011). Thereafter, daily surface temperatures (at 2 m) and precipitation were further downscaled to 4 km, and bias was corrected using the distribution-based scaling method (Yang et al, 2010) with reference data from the 4 km grid-based observations for 1981-2010. Finally, gridded values were transferred to each subbasin for the period 1961-2100 to force the S-HYPE model.…”
Section: Model Approach To the Past And The Futurementioning
confidence: 99%
“…Statistical downscaling and bias correction techniques involve empirical correction of simulated climate variables (e.g., precipitation and temperature) by fitting simulated means and quantiles to the available observations and applying the same correction to future simulations (e.g., Yang et al, 2010). Consequently, it is assumed that the observed biases in the mean and variability of those climate parameters are systematic and will be the same in the future, but it remains to be determined whether the climate model errors are static over time (Maraun et al, 2010).…”
Section: Downscaling and Bias Correctionmentioning
confidence: 99%
“…parts of the variable distribution). This is sometimes referred to as distribution-based scaling (DBS; Yang et al 2010;van Roosmalen et al 2011). Déqué (2007 and Piani et al (2010) gave a detailed description of the method.…”
Section: Bias Correction Methodsmentioning
confidence: 99%
“…Previous research (e.g., Hawkins & Sutton, 2009) has shown that towards the end of the 21st century, the emission scenarios (here RCPs) are the dominant source of uncertainty in climate projections; hence, our focus is on addressing only this source of uncertainty. The RCM projections (mean daily precipitation and temperature) were bias corrected against the APHRODITE and AphroTEMP datasets using the Distribution Based Scaling, DBS, statistical method (Yang et al, 2010) to obtain a reliable impression of the climate change. In brief, DBS aims to match the quantile distribution of bias-corrected data (precipitation and temperature) to the one of the reference data.…”
Section: Climate Scenariosmentioning
confidence: 99%
“…Three projections using emission scenarios RCP2.6, RCP4.5 and RCP8.5 are examined to provide information on the uncertainty in the climate projections. The state of the art bias-correction method Distribution Based Scaling (Yang et al, 2010) was used to improve on relevant biases for hydrological impact modelling in the area. Finally, the bias-corrected CORDEX-SA projections were introduced into the HYPE (HYdrological Predictions for the Environment) hydrological model to assess the impact of climate change on water over the Luni region.…”
Section: Introductionmentioning
confidence: 99%